Dampak Tempat Pelelangan Ikan Terhadap Kondisi Sosial Ekonomi Masyarakat Di Desa Asemdoyong Kecamatan Taman Kabupaten Pemalang Tahun 2019 - Hikhmatul Rizki; Khasanah Khasanah; Waskito Waskito (Indonesian Journal of Geography Education, 2020)
The purpose of this study was to identify the facilities and infrastructure of the fish auction place, to analyze the fish auction place, to find out the level of efficiency of the fish auction place in Asemdoyong village, and to determine the impact of the fish auction place on the socio-economic conditions of the community.In this study the authors used qualitative methods. Research location Asemdoyong Village Fish Auction Place. Data collection uses interviews, observations, and documentation to auction officers, fishermen, and visitors. Data validity is done by triangulation of sources, because in this study the data obtained will be collected and know the truth.The results of this study are in Asemdoyong Village there is a fishery port which is used as a fish auction market from fishermen's catches whose heads unload at Asemdoyong TPI, auction payments are made in cash, if not cash, payment is made maximum 1 (one) day after auction implementation. Asemdoyong TPI has complete facilities in the form of a large and strategic building, a dock for loading and unloading fishermen's catches, has drainage channels, there is a TPI supervisor post office, a water tower, a fish drying area, a fishing boat hut, and places to eat. the surrounding community is very active in the auction site, because some of the Asemdoyong villagers work in the port, both men and women. With the presence of TPI in Asemdoyong village, many visitors from various regions come and this is very beneficial for TPI and the surrounding residents who have a shop or shop business and this can improve the socio-economic situation of their people.